2004
DOI: 10.1177/153303460400300109
|View full text |Cite
|
Sign up to set email alerts
|

Improved Display of Synthetic IgG-Binding Domains on the Baculovirus Surface

Abstract: Improved display of foreign protein moieties in combination with beneficial alteration of the viral surface properties should be of value for targeted and enhanced gene delivery. Here, we describe a vector based on Autographa californica multiple nucleopolyhedrovirus (AcMNPV) displaying synthetic IgG-binding domains (ZZ) of protein A fused to the transmembrane anchor of vesicular stomatitis virus (VSV) G protein. This display vector was equipped with a GFP/EGFP expression cassette enabling fluorescent detectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 36 publications
1
30
0
2
Order By: Relevance
“…16 The 21 amino-acid ectodomain of VSV-GED may retain these membrane-binding characteristics and thus mediate a stronger interaction with the target cell membrane. 18 This could also explain the difference observed in the transduction pattern in the rat brain of the VSV-GED-pseudotyped virus when compared with the control virus. However, when it is taken into account that baculoviruses are able to enter numerous cell lines, 22,28,29 the reason for the observed enhanced gene expression in vivo is less likely due to the increased virus attachment than augmented endosomal release.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…16 The 21 amino-acid ectodomain of VSV-GED may retain these membrane-binding characteristics and thus mediate a stronger interaction with the target cell membrane. 18 This could also explain the difference observed in the transduction pattern in the rat brain of the VSV-GED-pseudotyped virus when compared with the control virus. However, when it is taken into account that baculoviruses are able to enter numerous cell lines, 22,28,29 the reason for the observed enhanced gene expression in vivo is less likely due to the increased virus attachment than augmented endosomal release.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, it has been demonstrated that the GS-region of VSV-G can be used as a membrane anchor in displaying fusion proteins on baculovirus surface. 17, 18 Yet, a vector displaying a fusion protein of IgG-domain (ZZ) of protein A fused to the VSV-GED did not result in increased transduction efficiency. 18 In the current study, we constructed a baculovirus vector displaying, in addition to gp64, a 21-amino-acid ectodomain in conjunction with the TM and CTD domains of VSV-G (VSV-GED) and studied its effect on the baculovirus infection and transduction rates in insect and vertebrate cells, respectively.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Although modification of the virion surface enhances the efficiency of gene transduction into a variety of cell lines, the utility of recombinant baculoviruses in cell-type-specific gene transduction is still unsatisfactory. Ojala et al demonstrated that, while baculoviruses bearing either a single chain antibody fragment specific for carcinoembryonic antigen or a synthetic immunoglobulin G (IgG) binding domain derived from protein A could specifically bind target cells, cell type-specific gene transduction was unsuccessful (44,45). Although gp64-null pseudotype baculoviruses expressing a foreign viral envelope protein, such as VSVG or fusion envelope glycoproteins from other baculoviruses, exhibited high infectivity to insect cells, their capacity for gene transduction into mammalian cells has yet to be explored (33,34).…”
mentioning
confidence: 99%
“…We propagated Autographa californica nuclear polyhedrosis virus (AcNPV; ATCC); its derivative AcCOPSNo10 (16 ), which displays a 17-amino acid epitope of HIV-1 gp120 N-terminally fused with a second copy of the major envelope protein gp64; and the construct AcZZVSVgTM-EGFP (17 ) in Sf9 (Spodoptera frugiperda; ATCC) with standard methods (18 ). We used modified IPL-41 (16 ) from Sigma-Aldrich as medium.…”
Section: Materials and Methods Virusesmentioning
confidence: 99%